1994
DOI: 10.1139/x94-226
|View full text |Cite
|
Sign up to set email alerts
|

Variation in susceptibility of Eucalyptusglobulus provenances to Mycosphaerella leaf disease

Abstract: Quantitative assessments of the incidence and severity of Mycosphaerella leaf disease were made on nine provenances (encompassing the four subspecies) of Eucalyptusglobulus Labill. over three seasons in 1990 in a trial in Victoria, Australia. Defoliation was also assessed and tree height and diameter measured. Mycosphaerella leaf disease increased rapidly from winter to spring with disease incidence reaching 100% in most provenances by summer. There were highly significant differences in disease severity among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
5
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 0 publications
3
77
5
1
Order By: Relevance
“…The detection of significant genetic variation in MLD damage at the population and family within population level, accords with previous smaller-scale studies (Carnegie et al, 1994;Dungey et al, 1997;Hood et al, 2002;Carnegie and Ades, 2005), although a higher heritability was reported by Milgate et al (2005a) in a trial that experienced a very severe MLD epidemic. Negative genetic correlations between MLD damage and growth in E. globulus trials severely affected by disease have been reported in past studies (Carnegie et al, 1994;Milgate et al, 2005a), representing a possible mechanism for (i) future breeding for more rapid growth and (ii) past pathogenimposed selection for greater MLD resistance in disease prone environments.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The detection of significant genetic variation in MLD damage at the population and family within population level, accords with previous smaller-scale studies (Carnegie et al, 1994;Dungey et al, 1997;Hood et al, 2002;Carnegie and Ades, 2005), although a higher heritability was reported by Milgate et al (2005a) in a trial that experienced a very severe MLD epidemic. Negative genetic correlations between MLD damage and growth in E. globulus trials severely affected by disease have been reported in past studies (Carnegie et al, 1994;Milgate et al, 2005a), representing a possible mechanism for (i) future breeding for more rapid growth and (ii) past pathogenimposed selection for greater MLD resistance in disease prone environments.…”
Section: Discussionsupporting
confidence: 90%
“…The severity of MLD on each tree was visually assessed as the percentage of leaf area necrosis in the entire juvenilecrown using the disease assessment diagrams presented in Carnegie et al (1994). Negligible defoliation because of MLD had occurred at the time of assessment.…”
Section: Traits Assessedmentioning
confidence: 99%
“…T. pseudonubilosa is a sister species to T. nubilosa and in all prior studies, these two fungi have been treated collectively. It will, therefore, be necessary to reexamine all previous disease situations and tree improvement studies (e.g., Carnegie and Ades 2003;Carnegie et al 1994Carnegie et al , 1998 where T. nubilosa sensu lato has been implicated and to determine whether there might be differences in the host range and ecology of the two pathogens. This should not be difficult because the four fixed nucleotide characters in the ITS gene region are diagnostic and for many previous studies, sequence data are available in GenBank (Crous et al 2004;Glen et al 2007;Hunter et al 2004bHunter et al , 2009Kularatne et al 2004;Maxwell et al 2001;Pérez et al 2009a, b).…”
Section: Discussionmentioning
confidence: 99%
“…These fungi cause leaf spots, leaf blotches, or petiole and stem cankers that often result in stressed and stunted trees, adversely affecting commercial forestry operations (Carnegie et al 1994;Carnegie et al 1998;Lundquist and Purnell 1987;Park et al 2000;Sanchez Marquez et al 2011).…”
Section: A Diverse Group Of Mycosphaerellaceae and Teratosphaeriaceaementioning
confidence: 99%